How lithium sulfide is produced

JP7651096B2Active Publication Date: 2025-03-26HONJIYOU CHEM
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021121110
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-22
Publication Date
2025-03-26
Estimated Expiration
2041-07-22

AI Technical Summary

Benefits of technology

【0014】 本発明に従って、硫酸リチウムを硫黄及び還元剤と共に不活性雰囲気下又は還元性雰囲気下に焼成することによって、炭酸リチウムの副生なしに、又は殆どなしに、高純度の硫化リチウムを得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651096000002
    Figure 0007651096000002
  • Figure 0007651096000003
    Figure 0007651096000003
  • Figure 0007651096000001
    Figure 0007651096000001
Patent Text Reader

Abstract

To provide a method for obtaining lithium sulfide of high purity by reducing lithium sulfate with a reductant with no or little by-production of lithium carbonate.SOLUTION: Lithium sulfate is calcined together with sulfur or a reductant in an inert atmosphere or a reducing atmosphere. Here, powdery sulfur is preferably used as the sulfur, and 0.26 mole of the sulfur is preferably used relative to 1 mole of lithium sulfate. As the reductant, at least one kind selected from the group consisting of saccharides, polyhydric alcohols and porous carbon materials is preferably used. Among these, the saccharides or the polyhydric alcohols are preferable and, specifically, sucrose is preferably used.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing lithium sulfide, and more particularly to a method for producing lithium sulfide by reducing lithium sulfate with a reducing agent, thereby obtaining high-purity lithium sulfide, in a preferred case, without producing lithium carbonate as a by-product. [Background technology]

[0002] Lithium sulfide is useful as a raw material for solid electrolytes and positive electrode materials for lithium batteries, a raw material for synthesizing polyphenylene sulfide resin, an intermediate raw material for chemicals, and the like.

[0003] Conventionally, as a method for producing lithium sulfide, for example, a method for obtaining lithium sulfide by reacting lithium hydroxide with hydrogen sulfide in an aprotic organic solvent such as N-methyl-2-pyrrolidone is known (see Patent Document 1). However, in such a method, a complicated and expensive reaction apparatus is required because hydrogen sulfide is used, and further, the organic solvent itself is expensive. In addition, after producing lithium sulfide, the organic solvent needs to be treated, which results in a problem of high production costs.

[0004] Several methods for producing lithium sulfide using lithium carbonate as a raw material without using an organic solvent have been proposed. For example, a method has been proposed in which lithium sulfide is obtained by contacting lithium carbonate with hydrogen sulfide in a fluidized state at high temperatures (see Patent Document 2). This method requires a complex and expensive reaction apparatus to contact lithium carbonate with hydrogen sulfide in a fluidized state.

[0005] Therefore, a method has been proposed in which lithium sulfate is mixed with a reducing agent and the mixture is baked in a reaction vessel under a nitrogen gas atmosphere to obtain lithium sulfide (see Patent Documents 3 and 4). According to this method, theoretically, when 1 mole of lithium sulfate is reacted with 2 moles of carbon (reducing agent), 1 mole of lithium sulfide is produced and 2 moles of carbon dioxide gas is generated.

[0006] However, in reality, in the above-mentioned method, the reaction does not proceed as theoretically expected, sulfur dioxide gas and carbon monoxide gas are generated, and the obtained lithium sulfide often contains lithium carbonate as a by-product. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 7-330312 [Patent Document 2] JP 2013-75816 A [Patent Document 3] JP 2013-227180 A [Patent Document 4] JP 2016-216349 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the above-mentioned problems in the production of lithium sulfide, and has an object to provide a method for obtaining high-purity lithium sulfide without or almost without the by-production of lithium carbonate by reducing lithium sulfate with a reducing agent. [Means for solving the problem]

[0009] According to the present invention, there is provided a method for producing lithium sulfide, which comprises calcining lithium sulfate together with sulfur and a reducing agent in an inert atmosphere or a reducing atmosphere.

[0010] In the present invention, it is preferable to use powdered sulfur as the sulfur, and it is preferable to use 0.26 mol or more of sulfur per 1 mol of lithium sulfate.

[0011] The reducing agent is preferably at least one selected from the group consisting of sugars, polyhydric alcohols, and porous carbon materials, of which sugars and polyhydric alcohols are preferred, and sucrose is particularly preferred.

[0012] When an organic compound such as a sugar or a polyhydric alcohol is used as the reducing agent, it is preferable to heat lithium sulfate together with sulfur and the reducing agent in the presence of an antifoaming agent under an inert atmosphere or a reducing atmosphere.

[0013] As the defoaming agent, vegetable oil is preferably used. Effect of the Invention

[0014] According to the present invention, by calcining lithium sulfate together with sulfur and a reducing agent under an inert atmosphere or a reducing atmosphere, it is possible to obtain high-purity lithium sulfide without or with almost no by-production of lithium carbonate. [Brief description of the drawings]

[0015] [Figure 1] 1 shows powder X-ray diffraction patterns of lithium sulfide obtained in Examples 1 to 5. [Diagram 2] 1 shows powder X-ray diffraction patterns of lithium sulfide obtained in Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The method for producing lithium sulfide according to the present invention is characterized in that lithium sulfate is calcined together with sulfur and a reducing agent in an inert atmosphere or a reducing atmosphere.

[0017] The lithium sulfate used in the present invention may be anhydrous or monohydrate. In either case, commercially available products can usually be used.

[0018] In the present invention, when lithium sulfate is mixed with sulfur and a reducing agent to obtain a mixture, it is preferable to pulverize the lithium sulfate using, for example, a hammer mill so that the resulting mixture is homogeneous. However, the average particle size of the pulverized product is not particularly limited. The hammer mill is not particularly limited, and for example, Bantam Mill AP-B manufactured by Hosokawa Micron Corporation can be used.

[0019] According to the present invention, lithium sulfate is mixed with sulfur and a reducing agent, and the resulting mixture is calcined. The means for this mixing is not particularly limited, and for example, a micro speed mixer manufactured by Takara Koki Co., Ltd. can be used.

[0020] As described above, according to the present invention, by using sulfur in the coexistence of lithium sulfate when it is calcined together with a reducing agent to reduce it, it is possible to obtain high-purity lithium sulfide without or with almost no by-production of lithium carbonate.

[0021] Sulfur is known in various forms such as rubber, crystal, powder, etc. In the present invention, the sulfur used is preferably powdered sulfur so that it can be easily mixed with lithium sulfate and a reducing agent. However, the sulfur used in the present invention is not limited to powdered sulfur.

[0022] In the present invention, sulfur is used in an amount of 0.26 molar parts or more per molar part of lithium sulfate. When the amount of sulfur used is less than 0.26 molar parts per molar part of lithium sulfate, the resulting lithium sulfide contains lithium carbonate. When lithium sulfide is calcined together with a reducing agent in the absence of sulfur, the resulting lithium sulfide contains a larger amount of lithium carbonate.

[0023] There is no particular upper limit on the amount of sulfur used, but since using too much sulfur will not produce a corresponding effect, the amount is usually 1.0 part by mole per 1 part by mole of lithium sulfate.

[0024] The reducing agent is preferably at least one selected from the group consisting of sugars, polyhydric alcohols, and porous carbon materials. Preferred examples of sugars include monosaccharides such as fructose, and disaccharides such as sucrose and lactose. Among them, sucrose is particularly preferred in the present invention.

[0025] As the polyhydric alcohol, for example, ascorbic acid and polyvinyl alcohol can be mentioned as preferred examples, with ascorbic acid being particularly preferred.As a specific example of a preferred porous carbon material, for example, activated carbon can be mentioned.

[0026] The reducing agent is used at a molar ratio (C / O2) of carbon atoms in the reducing agent to O2 in lithium sulfate (Li2SO4) of preferably 1.60 or more. Hereinafter, for simplicity, the molar ratio (C / O2) of carbon atoms in the reducing agent to O2 in lithium sulfate (Li2SO4) is referred to as the carbon ratio of the reducing agent.

[0027] When lithium sulfate is calcined together with a reducing agent to obtain lithium sulfide, if the carbon ratio of the reducing agent is less than 1.60, lithium carbonate may be by-produced. On the other hand, if the carbon ratio of the reducing agent is more than 1.80, the amount of carbon remaining in the calcined product may increase. Therefore, in the present invention, although not necessarily limited, the carbon ratio of the reducing agent is preferably in the range of 1.60 to 1.80.

[0028] In the present invention, when lithium sulfate is mixed with sulfur and a reducing agent and the resulting mixture is baked, depending on the reducing agent used, for example, when sucrose is used as the reducing agent, the reducing agent may generate foam.

[0029] Therefore, when the mixture is baked using, for example, sucrose as a reducing agent, it is preferable to use an antifoaming agent in the presence of the antifoaming agent, which is preferably an animal fat or vegetable fat, more preferably a vegetable fat, and most preferably a vegetable oil.

[0030] Examples of the vegetable oil include rapeseed oil, canola oil, soybean oil, corn oil, cottonseed oil, safflower oil, sesame oil, olive oil, palm oil, rice oil, grape oil, etc., and edible vegetable oils are particularly preferred, but are not limited to these.

[0031] In the present invention, salad oil obtained by highly refining a single vegetable oil is also preferably used as a defoaming agent instead of the above vegetable oils. The salad oil may be a blended salad oil containing two or more kinds of vegetable oils.

[0032] The amount of the antifoaming agent used is not particularly limited, but may usually be in the range of 0.1 to 1% by weight of the amount used, even if the lithium sulfate used is anhydrous or monohydrate.

[0033] According to the present invention, lithium sulfate, sulfur, a reducing agent, and optionally an antifoaming agent are mixed in this manner to obtain a homogeneous mixture, which is then calcined in an inert or reducing atmosphere.

[0034] In the present invention, the calcination temperature is preferably in the range of 850 to 950° C., and more preferably in the range of 870 to 930° C. The calcination time at the calcination temperature is usually in the range of 5 to 10 hours so that no unreacted lithium sulfate remains. In such calcination, the temperature rise time from room temperature to the calcination temperature and the temperature fall time from the calcination temperature to room temperature are also not particularly limited, but are usually about 3 to 10 hours, and preferably about 4 to 8 hours.

[0035] After the above-mentioned calcination is completed, the obtained calcined product, i.e., lithium sulfide, can be obtained as a powder by pulverizing in an inert gas atmosphere and then sieving. EXAMPLES

[0036] The production of lithium sulfide according to the present invention will be described below based on examples. The anhydrous lithium sulfate used below has a purity of 96.0% by weight.

[0037] In the following, the average particle size of anhydrous lithium sulfate after pulverization was determined by determining the volume-based particle size distribution by dry measurement using a Microtrac MT3300EX II by a laser diffraction / scattering method, and the average particle size was calculated on a volume basis.

[0038] The powder X-ray diffraction of the obtained lithium sulfide was measured using an Ultima IV X-ray diffractometer manufactured by Rigaku Corporation. Measurement conditions Target: Cu-Kα Tube voltage: 40kV Tube current: 40mA Operation speed: 4° / min

[0039] Example 1 276.7 g (2.42 mol) of anhydrous lithium sulfate, which had been pulverized to an average particle size (D50) of 40 μm using a hammer mill "Bantam Mill AP-B" manufactured by Hosokawa Micron Corporation, and 26.3 g (0.82 mol, 0.34 mol parts per 1 mol part of anhydrous lithium sulfate) of powdered sulfur were charged into a micro speed mixer manufactured by Takara Kogyo Co., Ltd., and mixing was performed twice for 5 minutes.

[0040] Next, 223.3 g (0.65 mol, carbon ratio of the reducing agent: 1.62) of sucrose and 0.8 g of canola oil (manufactured by Showa Sangyo Co., Ltd.; the same applies below) were added to the mixer, and mixing was performed twice for 5 minutes.

[0041] The mixture was filled in an alumina crucible, the crucible was placed in a metal container, and the metal container was placed in an electric furnace. After the electric furnace was filled with a nitrogen gas atmosphere, the electric furnace temperature was raised from room temperature to 930°C over 5 hours, and the electric furnace temperature was maintained at this temperature for 6 hours. Thereafter, the electric furnace temperature was cooled to room temperature over 6 hours. In this manner, the mixture was fired under a nitrogen gas atmosphere.

[0042] After the firing was completed, the crucible was removed from the electric furnace and stored in an airtight container. It was then transferred to a glove box in an argon gas atmosphere. The fired product was then removed from the crucible and pulverized using a small pulverizer SK-M10 sample mill manufactured by Kyoritsu Riko Co., Ltd., and sieved through a sieve with 1 mm openings to obtain lithium sulfide as a powder.

[0043] Example 2 Lithium sulfide was obtained in powder form in the same manner as in Example 1, except that the amount of powdered sulfur was 15.7 g (0.49 mol, 0.27 parts by mol per 1 part by mol of anhydrous lithium sulfate).

[0044] Example 3 Lithium sulfide was obtained in powder form in the same manner as in Example 1, except that the amount of powdered sulfur was 55.6 g (1.73 mol, 0.72 mol parts per 1 mol part of anhydrous lithium sulfate).

[0045] Example 4 Lithium sulfide was obtained as a powder in the same manner as in Example 1, except that the amount of sucrose used was 220.5 g (0.64 mol, carbon ratio of the reducing agent was 1.60).

[0046] Example 5 In Example 1, lithium sulfide was obtained as a powder in the same manner as above, except that 276.7 g (2.42 mol) of anhydrous lithium sulfate, 26.3 g (0.82 mol, 0.34 molar parts per 1 molar part of anhydrous lithium sulfate), and 230.6 g (1.31 mol, carbon ratio of the reducing agent is 1.62) of L-ascorbic acid and 0.8 g of canola oil were used instead of the reducing agent sucrose.

[0047] Comparative Example 1 Lithium sulfide was obtained as a powder in the same manner as in Example 1, except that the amount of powdered sulfur was 15.5 g (0.48 mol, 0.20 mol parts per 1 mol part of anhydrous lithium sulfate). As a result of X-ray diffraction analysis, a lithium carbonate peak was observed on the (002) plane.

[0048] Comparative Example 2 Lithium sulfide was obtained as a powder in the same manner as in Example 1, except that the amount of sucrose used was 206.8 g (0.60 mol, carbon ratio of the reducing agent was 1.50). As a result of X-ray diffraction analysis, lithium carbonate peaks were observed on the (002), (110), and (-311) planes.

[0049] Comparative Example 3 In the same manner as in Example 1, 276.7 g (2.42 mol) of anhydrous lithium sulfate pulverized to an average particle size (D50) of 40 μm and 223.3 g (0.65 mol, carbon ratio of the reducing agent is 1.62) of sucrose were charged and mixed twice for 5 minutes. Next, 0.8 g of canola oil was added to the mixture, and the mixture was mixed twice for 5 minutes.

[0050] The obtained mixture was filled into an alumina crucible, and the crucible was placed in a metal container, which was then housed in the same electric furnace as in Example 1. After the electric furnace was filled with a nitrogen gas atmosphere, the electric furnace temperature was raised from room temperature to 930°C over a period of 5 hours, and the electric furnace temperature was maintained at this temperature for 6 hours, after which the electric furnace temperature was cooled to room temperature over a period of 6 hours, and thus the mixture was fired under a nitrogen gas atmosphere.

[0051] After the firing, the crucible was removed from the electric furnace and stored in a sealed container, and then transferred to a glove box in an argon gas atmosphere, where the fired product was removed from the crucible and crushed and sieved through a sieve with 1 mm openings in the same manner as in Example 1 to obtain lithium sulfide powder. As a result of X-ray diffraction analysis, lithium carbonate peaks were observed on the (002) and (110) planes.

[0052] Table 1 shows the results of the X-ray diffraction analysis for the above examples and comparative examples.

[0053] [Table 1]

[0054] In the analysis of the powder X-ray diffraction patterns in Table 1, the relative intensity of lithium carbonate to lithium sulfide is a value calculated as (b / a) × 100, where a (cps) is the diffraction intensity based on lithium sulfide and b (cps) is the diffraction intensity based on lithium carbonate.

[0055] In the analysis of the powder X-ray diffraction pattern of the obtained lithium sulfide, no diffraction peak due to lithium carbonate was observed in the obtained lithium sulfide in any of Examples 1 to 5 (ND).

[0056] In Comparative Example 1, the sulfur / lithium sulfate molar ratio was less than 0.26, and the resulting lithium sulfide had a diffraction peak due to lithium carbonate. In Comparative Example 2, the carbon ratio of the reducing agent was less than 1.60, and the resulting lithium sulfide had a diffraction peak due to lithium carbonate. In Comparative Example 3, lithium sulfate was calcined together with a reducing agent in the absence of sulfur, and the resulting lithium sulfide had a diffraction peak due to lithium carbonate with a stronger intensity than Comparative Examples 1 and 2.

[0057] FIG. 1 shows the X-ray diffraction patterns of the lithium sulfides obtained in Examples 1 to 5 in which the diffraction angle 2θ is in the range of 20 to 38°, and FIG. 2 shows the X-ray diffraction patterns of the lithium sulfides obtained in Comparative Examples 1 to 3 in which the diffraction angle 2θ is in the range of 20 to 38°.

[0058] The diffraction angle of the (111) plane of lithium sulfide is 26.98°, the diffraction angle of the (002) plane of lithium carbonate is 31.78°, and the diffraction angle of the (110) plane of lithium carbonate is 21.33°.

[0059] As shown in FIG. 2, in the X-ray diffraction patterns of the lithium sulfides obtained in Comparative Examples 1 to 3, diffraction peaks due to the (002) plane and the (110) plane due to lithium carbonate were observed. However, as shown in FIG. 1, in the X-ray diffraction patterns of the lithium sulfides obtained in Examples 1 to 5, neither diffraction peaks due to the (002) plane nor diffraction peaks due to the (110) plane due to lithium carbonate were observed.

[0060] The diffraction angle of the (-311) plane of lithium carbonate is 36.96°. In the X-ray diffraction patterns of the lithium sulfides obtained in Comparative Examples 1 to 3, a diffraction peak due to the (-311) plane due to lithium carbonate is observed, but in the X-ray diffraction patterns of the lithium sulfides obtained in Examples 1 to 5, as shown in FIG. 1, no diffraction peak due to the (-311) plane was observed.

Claims

1. A method for producing lithium sulfide, comprising calcining lithium sulfate together with sulfur and a reducing agent under an inert atmosphere or a reducing atmosphere, The sulfur is used in an amount of 0.26 molar parts or more and 0.72 molar parts or less relative to 1 molar part of the lithium sulfate, A method for producing lithium sulfide, wherein a molar ratio (C / O 2 ) of carbon atoms in the reducing agent to oxygen in the lithium sulfate is 1.6 or more and 1.8 or less.

2. The method for producing lithium sulfide according to claim 1, wherein powdered sulfur is used as the sulfur.

3. 2. The method for producing lithium sulfide according to claim 1, wherein the reducing agent is at least one selected from the group consisting of sugars, polyhydric alcohols, and porous carbon materials.

4. The method for producing lithium sulfide according to claim 3, wherein the sugar is sucrose.

5. The method for producing lithium sulfide according to claim 3, wherein the polyhydric alcohol is ascorbic acid.

6. The method for producing lithium sulfide according to claim 3, wherein the porous carbon material is activated carbon.

7. The method for producing lithium sulfide according to claim 1, wherein lithium sulfate is calcined in the presence of an antifoaming agent.

8. The method for producing lithium sulfide according to claim 7, wherein the antifoaming agent is vegetable oil.

Citation Information

Patent Citations

  • Preparation method of lithium sulfide

    CN112678781A

  • Production of lithium sulfide

    JP1995330312A

  • Production of lithium sulfide

    JP1997278423A

  • Lithium sulfide, method for producing the lithium sulfide, and method for producing inorganic solid electrolyte

    JP2013075816A

  • Method for producing lithium sulfide

    JP2013227180A